A process-oriented modeling approach for graphical development of mobile business apps. (September 2018) - Rieger, Christoph; Kuchen, Herbert
Highlights: A graphical domain-specific language for model-driven business apps is proposed. Native mobile apps are generated from modeled use cases without manual programming. Data model inference disburdens the modeler from separate data model specification. Inferred knowledge allows for advanced modeling support in the graphical editor. In contrast to IFML, the notation is also understandable for non-technical users. Abstract: Mobile app development is an activity predominantly performed by software developers. Domain experts and future users are merely considered in early development phases as source of requirements or consulted for evaluating the resulting product. In the domain of business apps, many cross-platform programming frameworks exist but approaches also targeted at non-technical users are rare. Existing graphical notations for describing apps either lack the simplicity to be understandable by domain experts or are not expressive enough to support automated processing. The MAML framework is proposed as model-driven approach for describing mobile apps in a platform-agnostic fashion not only for software developers but also for process modelers and domain experts. Data, views, business logic, and user interactions are jointly modeled from a process perspective using a graphical domain-specific language. To aggregate multiple use cases and provide advanced modeling support, an inference mechanism is utilized to deduce a global data model. Through model transformations, native apps are then automatically generated for multiple platforms without manual programming. Our approach is compared to the IFML notation in an observational study, with promising results regarding readability and usability.